2018
DOI: 10.1002/htj.21369
|View full text |Cite
|
Sign up to set email alerts
|

Rarefaction and external force effects on gas microflow in a lid‐driven cavity

Abstract: In this paper, the regularized 13‐moment approach (R13) is used to investigate the rarefaction effect on rarefied gas flow within a lid‐driven cavity. We will discuss the validity domain of the Navier‐Stokes and Fourier (NSF) solutions using the first order of velocity slip and temperature jump boundary conditions (NSF) and the regularized 10‐moments (R10) in slip and early transition regime. The effect of an external body force is examined in different directions according to the cavity inclination angle. A M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 37 publications
0
7
0
Order By: Relevance
“…Accordingly, many experimental 5,6 and theoretical 7,8 efforts have been made to investigate the natural convection heat transfer over decades. Different numerical models have been also addressed as an area of great interest for studying heat transfer, which is mostly based upon the conventional Navier‐Stokes (N‐S) equations 9 …”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, many experimental 5,6 and theoretical 7,8 efforts have been made to investigate the natural convection heat transfer over decades. Different numerical models have been also addressed as an area of great interest for studying heat transfer, which is mostly based upon the conventional Navier‐Stokes (N‐S) equations 9 …”
Section: Introductionmentioning
confidence: 99%
“…Lid-driven cavity flow is one of the classical benchmark problems of computational fluid dynamics (CFD) [2][3][4][5]. Such flow has been analyzed by various computational methods like the Navier-Stokes-Fourier equations (NSF) [6,7], Direct Simulation Monte Carlo (DSMC) [7][8][9][10] and moment equations approach [6,10,11].…”
Section: Introductionmentioning
confidence: 99%
“…The main simulation parameters are the Knudsen number (Kn) and the tangential momentum accommodation coefficient σ (TMAC). Unlike the DSMC method which needs a long computation time to give satisfactory results [28] and the extended macroscopic theory, like regularized 13 moment (R13), which the range of validity is limited [6,29], the MRT-LBM proved its effectiveness for rarefied gas simulation.…”
Section: Introductionmentioning
confidence: 99%
“…The difference between them lies in the relations for higher order moments [8,9]. It has been shown that all variants are well applicable for numerical modelling of the moderately rarefied slow gas flows and allow the modelling of main nonequilibrium effects in low-velocity micro-flow problems [10,11,12,13,14,15,16,17] and some moderately rarefacted supersonic flows [5,18,19,15,20,21,22]. The difficulty is that the solid wall boundary conditions for R13 equations were obtained from one of the variants [10] which is not applicable to near hypersonic flows [9].…”
Section: Introductionmentioning
confidence: 99%